Realitas di Balik Narasi: Persepsi Sosial, Manajemen Keuangan, dan Kesejahteraan Psikososial Tenaga Kerja Indonesia sebagai Ekspatriat - Muhammad Hilmi Musyaffa'; Hafiyan Satrio Wibowo; Raden Mas Hugo Ello Satrio; Afrizal Dias Nugraha; Muhammad Rizky Atmasha; Hafid Kholidi Hadi, S.E., M.SM; Fresha Kharisma, S.E., M.SM. (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study investigates the social perceptions surrounding the lives of Indonesian migrant workers abroad, commonly referred to as expatriates, and examines the gap between these public perceptions and the actual experiences reported by workers themselves. Using a qualitative descriptive approach with in-depth interviews conducted with four informants working in South Korea, the United Arab Emirates, Germany, and Malaysia, this research explores five dimensions of expatriate life: social perceptions, financial management, social and cultural adaptation, mental and psychological conditions, and views on media representations of expatriate lifestyle. The findings reveal that social perceptions of expatriate life are predominantly shaped by selective content on social media and word-of-mouth narratives that emphasize prosperity while concealing complex realities. All informants reported significant discrepancies between public expectations and their lived experiences, including high cost of living, intense work pressure, cultural adaptation challenges, and persistent feelings of loneliness. Despite these challenges, informants demonstrated varying degrees of financial literacy and psychological resilience. The study highlights the critical importance of pre-departure financial education and psychological preparedness in supporting the well-being of Indonesian workers abroad. These findings contribute to the growing body of literature on expatriate adjustment and have practical implications for policies aimed at protecting and empowering Indonesian migrant workers.